2006
DOI: 10.1002/mus.20645
|View full text |Cite
|
Sign up to set email alerts
|

Double trouble (McArdle's disease and myasthenia gravis): How can exercise help?

Abstract: We report a 29-year-old patient with McArdle's disease and myasthenia gravis. She had been debilitated with McArdle's disease since childhood (with marked rhabdomyolysis) and was obese. Myasthenia gravis was diagnosed at 24 years of age. After 3 months of aerobic exercise training, her exercise capacity increased significantly and she regained the ability to live independently. We conclude that even patients with profound neuromuscular diseases may benefit from carefully prescribed exercise training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 11 publications
2
49
1
Order By: Relevance
“…These subjects had the highest functional status categories, although there was no difference in fatigue scores . A case report of a deconditioned woman with co‐existing McArdle disease and recently diagnosed MG described a significant improvement in her exercise capacity after 3 months of aerobic exercise training …”
Section: Overview Of Exercise Studies In Nmdmentioning
confidence: 97%
See 1 more Smart Citation
“…These subjects had the highest functional status categories, although there was no difference in fatigue scores . A case report of a deconditioned woman with co‐existing McArdle disease and recently diagnosed MG described a significant improvement in her exercise capacity after 3 months of aerobic exercise training …”
Section: Overview Of Exercise Studies In Nmdmentioning
confidence: 97%
“…77 A case report of a deconditioned woman with co-existing McArdle disease and recently diagnosed MG described a significant improvement in her exercise capacity after 3 months of aerobic exercise training. 78 Respiratory muscle training has benefitted MG patients in numerous trials; these trials used different classes of MG subjects, and most were nonrandomized. Fregonezi et al studied 27 patients with stable generalized MG who were randomized into training and control groups.…”
Section: Overview Of Exercise Studies In Nmdmentioning
confidence: 99%
“…This was followed by a 15 min warm-up period (free-wheel pedalling). We have previously used pre-exercise carbohydrate ingestion for V O 2 peak determination in McArdle patients with good results 14 – 18. Controls did not ingest the sucrose solution as we wanted to test them under normal conditions, that is, without artificially increased blood glucose before testing.…”
Section: Methodsmentioning
confidence: 99%
“…A program of moderate aerobic training was shown to improve exercise capacity and tolerance through an increase in oxidative capacity. 11,14,17 Although such an approach is both safe and efficacious, its general application needs long-term commitment. All patients with McArdle's disease should be advised to engage in regular monitored exercise, but it may be of interest to explore whether an ACE inhibitor such as ramipril offers additional benefit.…”
Section: Data Presented As Mean (Sd)mentioning
confidence: 99%
“…15 Despite increased understanding of the complex physiopathology and genetics of McArdle's disease, only limited advances have been made in effective therapy, mostly based on pre-effort sucrose ingestion and supervised exercise training. 4,11,14,17 Treatments directed toward increasing substrate availability to the exercising muscle have shown limited efficacy. 22 In a recent study 16 we demonstrated that a common insertion/deletion (I/D) polymorphism in the gene for angiotensin-converting enzyme (ACE) is associated with disease severity.…”
mentioning
confidence: 99%